Numerical simulation of the beam self-cleaning process in a multimode graded-index fibre during propagation of a pump wave and a Stokes component. (December 2020) - Sidelnikov, O.S.; Podivilov, E.V.; Babin, S.A.; Wabnitz, S.; Fedoruk, M.P.
Abstract: A model of coupled modes is proposed, which makes it possible to describe the propagation of a pump wave and a Stokes component in a multimode graded-index fibre. A decrease in the depression in the centre of the profile of the pump wave intensity distribution as a result of the influence of Kerr effects and random linear coupling of modes is demonstrated.